The Book That Was Destroyed in 1969: the Transgression of Literary and Pictorial Narratives by Ivan Drach and Tetyana Yablonska. - Паранюк, Дан; Тичініна, Альона (Georgian Comparative Literature Association, 2023)
Since socialist realism mostly appears as a complete aesthetic and cultural paradigm, which is closely related to the previous historical stage, its experience seems to be both relevant and final at the same time. In Ukrainian culture, socialist realism is regarded as one of the most controversial periods when art became an ideological tool of influence. What is more, it is impossible to comprehensively assess the XX century Ukrainian literature without studying the canon of social realism. After Stalin’s death, socialist realism did not disappear at the stage of “decanonization” (1953-80s, according to G.Gunther); instead, its canon expanded, loosened, and got deformed.
Keywords: Social Realism, Ivan Drach, Tetyana Yablonska